Where have all the diseases gone during the COVID-19 pandemic? - Kohli, Anirudh; Shetty, Aditya; Joshi, Anagha; Bansal, Ashank (Indian Journal of Radiology and Imaging, 2021)
This article focuses on a marked drop in volumes in the lockdown period during the COVID-19 pandemic across all modalities X-ray, sonography, CT scan and MRI scans and compares the volumes of data between a private and public hospital in Mumbai. This trend has been witnessed globally also. Even with easing of lockdown this has not reflected in an increase in numbers. Imaging volumes of a 1900-bed public hospital and a 220-bed private hospital in Mumbai were collated for all modalities, i.e., X-ray, sonography, CT and MRI for the months January, February 2020- Prelockdown, March 2020 Peri-lockdown, April, May 2020- Lockdown, June Unlock 1.0, July Unlock 2.0. The imaging volumes during lockdown, Unlock, were compared with prelockdown values. It was initially felt that this was due to a fear of visiting hospitals that are considered hotbeds of SARS-CoV-2. However, the same status has persisted over the 2 months of lockdown and the 2 months of unlocking. What is the cause of this huge drop in imaging volumes?
Keywords: Covid -19 pandemic; lockdown; Mumbai hospitals; non-COVID; prelockdown; unlock